Marketing de serviços : agências funerárias (2019)
This dissertation aims to study the theme of Service Marketing in the sector of Funeral Agencies in Portugal, an area that has not yet been studied and which has a continuous business growth, given the high aging rate of the Portuguese population. This exploratory study had as its initial objectives: (i) to clarify the operation of this type of services in Portugal, since the beneficiary of the service is not alive and it is the relatives, friends or institutions that deal with these issues, (ii) present the business model of the activity of funeral agencies, since it has many stakeholders (iii) identify Marketing strategies in the creation of value through the offer of products and services. In this research work was literature review, web content analysis, statistical and financial data collection, with the objective of collecting information about the business of the Funeral Agencies, in a first phase. In the second phase of the study, three semi structured interviews were conducted, accompanied by a script, to entities representative of the sector in Portugal. The results of the study allow to clarify the sector, list the most requested services in the scope of a funeral and to realize what type of Marketing strategy has been carried out so far by the companies in this sector.